I Want to Fly - Ibrahimova, Maria (Azerbaijan, 2016)
Kamal has a dream: he wants to fly, but many say paragliding is an impossible dream
for a man in a wheelchair. An inspiration among the Paralympic community in Azerbaijan, he's helped
handicapped people to beat the odds. Now it's his turn to try.
Verzio Film Festival Submission
Keywords: Documentary films